Primary Angle-Closure Glaucoma: A Comprehensive Meta-Narrative Review - MacDonald, Derek (Canadian Journal of Optometry, 2025)
Absract Primary angle-closure glaucoma, while less common than primary open-angle glaucoma, carries a 4- to 5-fold greater risk of severe visual morbidity. The identification of individuals at high risk of the disease enables proactive rather than reactive intervention, which helps mitigate the possibility of potentially serious consequences. Recognition is facilitated by careful case history, clinical examination, and ancillary imaging, while management is an evolving paradigm, informed by a number of relatively recent investigations, that may involve medications, laser procedures, surgery, or a combination thereof. This series of 4 papers, drawing upon relevant peer-reviewed literature, will endeavour to provide a comprehensive yet focused synthesis and synopsis of the contemporary diagnosis and management of primary angle-closure glaucoma.